Method for preparing sound insulation material by using solid waste plastics

By using the modification and processing and process preparation of solid waste plastics, inorganic fibers, flame retardants and other materials, the existing sound insulation boards have solved the shortcomings in sound insulation effect stability, assembly convenience and material durability, and achieved the preparation of high-performance sound insulation materials, with good sound insulation effect, mechanical properties and environmental protection performance.

CN119552309AInactive Publication Date: 2025-03-04BEIJING BAHR TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411784371.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sound insulation panels in the exterior walls of the building have shortcomings in the long-term stability of the sound insulation effect, the convenience of assembly, the durability of the material and the environmental adaptability, resulting in the gradual reduction of the sound insulation effect, inconvenient installation, and aging of the material.

Method used

By collecting solid waste plastics, sorting, crushing and modifying, combining inorganic fibers, flame retardants and modifiers, and using twin-screw extruders and hot pressing treatment, high-performance sound insulation material sheets are prepared.

Benefits of technology

It improves the sound insulation effect, mechanical properties and weather resistance of sound insulation materials, enhances the flexibility and damping properties of the material, improves the interface bonding force with inorganic fibers, reduces the production and installation costs of the material, and has good environmental protection performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly materials, and particularly relates to a method for preparing a sound insulation material by using solid waste plastics, which comprises the following steps: collecting specific solid waste plastics, classifying and pre-treating, preparing two modifiers (VMPA and BHMPTS), respectively applying the two modifiers to different plastic systems, mixing with various additives, forming by a specific process, and post-treating to prepare a sound insulation exterior wall material. The material effectively solves the problem of solid waste plastic pollution, and improves the sound insulation, mechanical property, weather resistance and environmental protection performance. The sound insulation performance is remarkably improved in middle and low frequency bands, the mechanical property is enhanced, the weather resistance is good, and the release amount of harmful substances meets the standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of environmentally friendly materials, and in particular to a method for preparing sound insulation materials by utilizing solid waste plastics. Background Art

[0002] With the development of society and the improvement of people's requirements for quality of life, the sound insulation performance of building exterior walls has received more and more attention. In construction, sound insulation panels are usually used to enhance the sound insulation effect of exterior walls to create a quiet and comfortable indoor environment.

[0003] At present, there are some problems with the common sound insulation board technology for exterior walls of building construction on the market. For example, some sound insulation boards improve the sound insulation effect by installing a rubber layer, vibration-damping material or sound insulation felt between two boards. However, although this method can improve the sound insulation performance to a certain extent in the short term, as time goes by, materials such as rubber are prone to aging and hardening, losing elasticity, resulting in a gradual decrease in the sound insulation effect. Some sound insulation boards are assembled using card slots and splicing devices. This assembly method is inconvenient for partial disassembly and assembly in the later stage, which is not conducive to later maintenance and replacement, and increases the later maintenance cost. Moreover, the clamping force of the splicing device will weaken over time, which may cause the device to loosen or even fall off. After long-term use, the durability of the sound insulation materials of some sound insulation boards is also facing challenges. For example, some mineral fiber sound-absorbing materials, such as glass fiber and rock wool, have certain sound absorption properties, but their sound absorption properties may decline over time. The installation process of some sound insulation boards is also insufficient. During the installation process, if the construction quality is not high, thermal bridges may be generated, affecting the insulation effect and reducing durability. For example, poor sealing or the use of inferior materials will cause the insulation material to become damp and deform, thus affecting the overall sound insulation effect. In addition, the environmental adaptability of some sound insulation panels needs to be improved. In environments with strong ultraviolet radiation, severe wind and rain erosion, or large temperature changes, the performance of the sound insulation panels may be affected, leading to aging, deterioration, peeling, or water seepage, which in turn affects the sound insulation effect and durability.

[0004] Some existing patent technologies also have certain limitations. It uses rubber pads or sound insulation felts to insulate sound. Although it can improve the sound insulation effect in the short term, the sound insulation effect will gradually decrease after the aging of rubber and other materials; and it is not convenient to assemble and disassemble the parts later through the slots and splicing devices. The clamping force of the splicing device will gradually decrease, which may cause the device to loosen and fall off. The sound-absorbing protrusions and galvanized sheets are combined to form a wave shape to absorb noise, thereby improving the sound insulation performance. However, the structure of the sound-absorbing protrusions is relatively complex, which may increase the production cost and installation difficulty; at the same time, the method for improving the sound insulation effect is relatively single. Although the problem of reduced sound insulation effect after aging of sound insulation materials is solved, the setting of isolation barrels and other components in this scheme may make the overall structure relatively complex, and the improvement of sound insulation effect may be limited. When facing loud noise, it may not provide a sufficiently ideal sound insulation effect.

[0005] In summary, the existing building exterior wall sound insulation technology still has many areas that need to be improved and perfected in terms of long-term stability of sound insulation effect, convenience of assembly, durability of materials, and adaptability to complex environments. This urgently requires the development of a new type of building exterior wall sound insulation board to overcome the shortcomings of the existing technology and meet people's demand for high-quality sound insulation effect. Summary of the invention

[0006] The present invention provides a method for preparing a sound insulation material using solid waste plastics, comprising the following steps:

[0007] 1. Collect all kinds of solid waste plastics, including polyethylene (PE), polypropylene (PP), polystyrene

[0008] (PS) and other waste plastics are classified, screened, and crushed into small particles with a particle size of 2-5 mm to prepare inorganic fibers, flame retardants and coupling agents;

[0009] 2. Synthesize 4-vinyl-2-methoxyphenol acrylate (VMPA) modifier, mix it with solid waste plastic particles at a mass ratio of 1:15-1:8, add a coupling agent at a mass ratio of 1:10-1:5 to the modifier, and stir at high speed to evenly disperse the modifier;

[0010] 3. Add the solid waste plastic particles treated with the modifier, the inorganic fiber and the flame retardant into a twin-screw extruder for melt blending, extrude and shape into a plate with a thickness of 1-3 cm and cool and shape;

[0011] 4. After cooling and shaping, the plate is subjected to hot pressing treatment at a temperature of 150-180°C, a pressure of 10-20MPa, and a hot pressing time of 10-20 minutes, and then a silicone waterproofing agent coating is sprayed on the surface.

[0012] Further, the synthesis method of the VMPA modifier comprises:

[0013] 1. Add 4-hydroxy-3-methoxybenzaldehyde, hydroxyethyl acrylate, p-toluenesulfonic acid and toluene into a reaction kettle, heat to 80-100° C. and react for 4-6 hours, and obtain the intermediate product 4-(2-hydroxyethyl)-2-methoxyphenol acrylate (HEMPA) after treatment;

[0014] 2. HEMPA, triethylamine, hydroquinone and acryloyl chloride are reacted and treated to obtain pure VMPA.

[0015] Furthermore, the inorganic fiber is glass fiber or rock wool fiber, the flame retardant is aluminum hydroxide or zinc borate, and the coupling agent is silane coupling agent KH-550 or titanate coupling agent NDZ-201.

[0016] On the other hand, the present invention also provides another method for preparing a sound insulation material using solid waste plastics, comprising the following steps:

[0017] 1. Collect polyvinyl chloride (PVC) solid waste plastics, crush, clean and dry them, and prepare plasticizers, stabilizers and sound-absorbing fillers;

[0018] 2. Prepare bis(4-hydroxy-3-methylphenyl)sulfide (BHMPTS) modifier, mix it with PVC solid waste particles at a mass ratio of 1:12-1:6, add plasticizer at a mass ratio of 2:1-3:1 to the modifier and stabilizer at a mass ratio of 1:5-1:3 to the modifier, and knead to make the components evenly dispersed;

[0019] 3. Add the mixed materials and sound-absorbing fillers into an open mixer for mixing, and then press them into sound-insulating exterior wall material sheets through a flat vulcanizer;

[0020] The formed plate is subjected to plasma surface treatment and then coated with an intumescent fire retardant coating. Further, the preparation method of the BHMPTS modifier comprises:

[0021] 1. Under nitrogen protection, 4-methylphenol, carbon disulfide and sodium hydroxide are reacted, and the intermediate product bis(4-hydroxy-3-methylphenyl) disulfide (BHMPDS) is obtained by acidification, filtration and washing;

[0022] 2. BHMPDS was reacted in a hydrogen atmosphere using a Raney nickel catalyst to obtain pure BHMPTS.

[0023] Furthermore, the plasticizer is dioctyl phthalate (DOP), the stabilizer is calcium stearate, and the sound-absorbing filler is expanded perlite powder or vermiculite powder.

[0024] On the other hand, the present invention also provides a sound insulation exterior wall material prepared by the method, in which the VMPA modifier forms a cross-linked structure with solid waste plastics through vinyl, the methoxyl group and phenolic hydroxyl group improve the flexibility and damping performance of the material, the phenolic hydroxyl group enhances the interface bonding force with inorganic fibers, and the coupling agent improves the compatibility of each component.

[0025] On the other hand, the present invention also provides a sound insulation exterior wall material prepared by the method, in which the sulfide bond of the BHMPTS modifier improves the processing performance of PVC, the hydroxyl group improves the thermal stability of PVC and enhances the bonding strength with the sound-absorbing filler, the plasticizer improves flexibility, and the stabilizer improves long-term stability.

[0026] Beneficial technical effects:

[0027] The synthesized modifiers methoxy and phenolic hydroxyl can increase the flexibility and damping properties of the material, help absorb and dissipate sound wave energy, and thus improve the sound insulation effect. At the same time, phenolic hydroxyl can also form hydrogen bonds with active groups such as hydroxyl groups on the surface of inorganic fibers, enhance the interfacial bonding between solid waste plastics and inorganic fibers, and make the structure of the composite material more uniform and stable. At the same time, hydroxyl can also form hydrogen bonds with active groups on the surface of sound-absorbing fillers, enhance the bonding between the sound-absorbing fillers and the PVC matrix, and improve the dispersion of the sound-absorbing fillers in the matrix, thereby effectively improving the sound absorption and sound insulation performance of the material. DETAILED DESCRIPTION

[0028] Embodiment 1:

[0029] 1. Material Preparation

[0030] Collect all kinds of solid waste plastics, including but not limited to discarded plastic bottles, plastic films, plastic packaging, etc. such as polyethylene (PE), polypropylene (PP), and polystyrene (PS). Sort and screen the collected solid waste plastics, remove impurities (such as soil, metal pieces, etc.), and then crush them into small particles with a particle size of 2-5mm. Prepare auxiliary materials, such as inorganic fibers (such as glass fibers, rock wool fibers, etc.), flame retardants (such as aluminum hydroxide, zinc borate, etc.), and coupling agents (such as silane coupling agent KH-550, titanate coupling agent NDZ-201, etc.).

[0031] 2. Synthesis and addition of modifier

[0032] 1. Synthesis of a new modifier: 4-vinyl-2-methoxyphenol acrylate

[0033] (VMPA). Its synthesis method is as follows:

[0034] In a reactor with agitator, thermometer and reflux condenser, a certain amount of 4-hydroxy-3-methoxybenzaldehyde (e.g. 300g), hydroxyethyl acrylate (e.g. 250g) and p-toluenesulfonic acid (about 30g) are added as catalyst, and an appropriate amount of toluene is added as solvent. The reaction system is heated to 80-100°C and reacted for 4-6 hours under the condition of stirring speed of 300-500 rev / min. The generated water is continuously removed by a water separator during the reaction. After the reaction is completed, it is cooled to room temperature, washed to neutrality with a saturated sodium carbonate solution, then dried over anhydrous sodium sulfate, and finally toluene is removed by underpressure distillation to obtain an intermediate product 4-(2-hydroxyethyl)-2-methoxyphenol acrylate (HEMPA).

[0035] The obtained HEMPA (e.g. 400 g), triethylamine (about 50 g) and hydroquinone (about 5 g) are added to another reaction kettle, and then acryloyl chloride (e.g. 300 g) is slowly added dropwise, and the dropping speed is controlled to keep the reaction temperature at 0-5°C. After the dropwise addition is completed, the reaction is continued to stir at room temperature for 2-3 hours. After the reaction is completed, the mixture is washed with saturated brine, dried over anhydrous magnesium sulfate, and distilled under reduced pressure to obtain pure 4-vinyl-2-methoxyphenol acrylate (VMPA), with a yield of about 500-600 g.

[0036] The synthesized VMPA modifier is mixed with solid waste plastic particles in a mass ratio of 1:15-1:8, and an appropriate amount of coupling agent is added (the mass ratio of coupling agent to modifier is 1:10-1:5). The modifier is evenly dispersed on the surface of the solid waste plastic particles by high-speed stirring (stirring speed 800-1200 rpm, stirring time 20-30 minutes) to improve its compatibility with subsequent added materials.

[0037] 3. Composite material preparation

[0038] 1. Mix the solid waste plastic particles treated with modifiers with inorganic fibers (the mass ratio of solid waste plastic to inorganic fibers is 5:1-3:1), flame retardants (the mass ratio of flame retardants to solid waste plastics is 1:5

[0039] -1:3) is added into a twin-screw extruder for melt blending. The temperature of the twin-screw extruder is set to 180-220°C, the screw speed is 200-300 rpm, and the blending time is 10-15 minutes. During the blending process, the solid waste plastic is fully mixed with the inorganic fiber and the flame retardant to form a uniform composite material matrix.

[0040] 2. The melt-blended composite material is extruded through a die to form a plate with a thickness of 1-3 cm. The plate is then cooled and shaped by natural cooling or air cooling for 15-30 minutes to obtain a semi-finished product of the sound insulation exterior wall material.

[0041] 4. Post-processing and performance optimization

[0042] 1. Put the semi-finished product into the hot press for hot pressing treatment, the hot pressing temperature is 150-180℃, the pressure is 10-20MPa, and the hot pressing time is 10-20 minutes. Hot pressing treatment can further improve the density and strength of the material and improve the sound insulation performance. Spray a layer of waterproof and breathable coating, such as silicone waterproofing agent coating, on the surface of the hot-pressed board to improve the weather resistance and waterproof performance of the material, making it more suitable for use as an exterior wall material.

[0043] The synthesized VMPA modifier, the vinyl group in its molecular structure can undergo free radical polymerization reaction with the unsaturated bonds in the solid waste plastic to form a cross-linked structure, thereby improving the strength and stability of the material. The methoxy group and phenolic hydroxyl group can increase the flexibility and damping performance of the material, help absorb and dissipate sound wave energy, and thus improve the sound insulation effect. At the same time, the phenolic hydroxyl group can also form hydrogen bonds with active groups such as hydroxyl groups on the surface of inorganic fibers, thereby enhancing the interfacial bonding force between solid waste plastics and inorganic fibers, making the structure of the composite material more uniform and stable, and further improving the comprehensive performance of the material. The addition of a coupling agent can improve the compatibility between the modifier and solid waste plastics and inorganic fibers, and promote uniform dispersion and interaction between the components.

[0044] Embodiment 2:

[0045] 1. Raw material pretreatment

[0046] 1. Collect solid waste plastics, mainly polyvinyl chloride (PVC) solid waste, such as discarded PVC pipes, plastic doors and windows, etc. These PVC solid wastes are crushed, and the particle size after crushing is 1-3mm. Then wash the crushed PVC particles to remove dirt, oil and other impurities on the surface. You can use a combination of alkali washing (such as sodium hydroxide solution) and water washing, and then dry them to make the water content less than 0.5%. Prepare other additives, such as plasticizers (such as dioctyl phthalate DOP), stabilizers (such as calcium stearate), and sound-absorbing fillers (such as expanded perlite powder, vermiculite powder, etc.).

[0047] 2. Preparation and application of special modifiers

[0048] 1. Preparation of a new organic modifier: bis(4-hydroxy-3-methylphenyl) sulfide

[0049] (BHMPTS). Its preparation steps are as follows:

[0050] Under nitrogen protection, add 4-methylphenol (e.g. 400g), carbon disulfide (e.g. 200g) and sodium hydroxide (about 60g) into a reactor and stir evenly at a stirring speed of 200-400 rpm. Then slowly heat to 60-80°C and react for 3-5 hours. After the reaction is completed, cool to room temperature and add hydrochloric acid to acidify to pH = 1-2, at which time a yellow precipitate is generated. Filter and wash the precipitate with deionized water until it is neutral to obtain the intermediate product bis(4-hydroxy-3-methylphenyl) disulfide (BHMPDS).

[0051] Add BHMPDS (e.g. 300 g) to another reactor, add an appropriate amount of ethanol as a solvent, and then add Raney nickel catalyst (about 30 g). In a hydrogen atmosphere (hydrogen pressure is 2-4 MPa), heat to 80-100° C., and stir to react for 4-6 hours. After the reaction is completed, filter to remove the catalyst, and remove the ethanol by reduced pressure distillation to obtain pure bis(4-hydroxy-3-methylphenyl) sulfide (BHMPTS), with a yield of about 200-250 g.

[0052] 2. The prepared BHMPTS modifier is mixed with the pretreated PVC solid waste particles in a mass ratio of 1:12-1:6, and an appropriate amount of plasticizer (the mass ratio of plasticizer to modifier is 2:1-3:1) and stabilizer (the mass ratio of stabilizer to modifier is 1:5-1:3) is added.

[0053] The PVC particles are evenly dispersed in the internal mixer at a temperature of 160-190°C for 10-15 minutes to improve the processing performance and performance stability of the PVC.

[0054] 3. Composite material molding and performance improvement

[0055] 1. Mix the mixed material with the sound-absorbing filler (the mass ratio of PVC to the sound-absorbing filler is 4:1-2:1)

[0056] Add to the open mill for mixing, the mixing temperature is 150-170℃, the mixing time is 8-12 minutes. After mixing evenly, the material is pressed into shape by a flat vulcanizer, the pressing temperature is 170-200℃, the pressure is 15-25MPa, the pressing time is 10-15 minutes, and the sound insulation exterior wall material sheet is made.

[0057] 2. Surface treatment of the formed board can be carried out by using plasma treatment technology to introduce polar groups on the board surface, improve the surface hydrophilicity and roughness, and enhance the adhesion with the exterior wall paint. Then apply a layer of fire retardant paint, such as intumescent fire retardant paint, on the surface of the board to improve the fire resistance of the material so that it meets the fire protection requirements of the building exterior wall.

[0058] The thioether bond in the BHMPTS modifier has good flexibility and stability, which can improve the processing performance of PVC solid waste, reduce its melting temperature and melt viscosity, and make it easier to form. The hydroxyl group can interact with the chlorine atoms on the PVC molecular chain, etc., to improve the thermal stability of PVC and reduce thermal degradation during processing and use. At the same time, the hydroxyl group can also form hydrogen bonds with the active groups on the surface of the sound-absorbing filler, enhance the bonding force between the sound-absorbing filler and the PVC matrix, and improve the dispersibility of the sound-absorbing filler in the matrix, thereby effectively improving the sound absorption and sound insulation performance of the material. The addition of plasticizers can further improve the flexibility of the material, and stabilizers can help improve the stability of the material during long-term use to prevent aging and performance degradation.

[0059] Example 3

[0060] (I) Experimental setup

[0061] 1. Sample Preparation

[0062] 1. The first solution of Example 1 (marked as sample A), the second solution of Example 2 (marked as sample B), traditional sound insulation materials (such as rock wool board, marked as sample C) and boards directly prepared from solid waste plastics without modification (marked as sample D) were used as test samples. Each sample was prepared with the same specifications (such as 50cm×50cm

[0063] ×2cm) were used for various performance tests.

[0064] 2. Test items and methods

[0065] 1. Sound insulation performance test: Use acoustic testing equipment in a standard acoustic laboratory according to ISO

[0066] The test was conducted in accordance with the 140-3 standard. The test frequency range was 100-5000Hz, and the sound insulation (dB) at different frequencies was recorded.

[0067] 2. Mechanical properties test: including compressive strength and flexural strength test. The compressive strength test is carried out using a universal testing machine in accordance with GB / T 17657-1999 standard, with a loading speed of 1-2mm / min; the flexural strength test is carried out in accordance with GB / T 1936.1-2009 standard, with a span of 16 times the thickness of the plate and a loading speed of 2-5mm / min.

[0068] 3. Weathering test: Place the sample in an artificial weathering chamber to simulate the light in the natural environment (ultraviolet intensity is 50-100W / m 2), temperature change (-20℃-60℃), humidity (40%-90%) and other conditions, the aging time is 1000-2000 hours. The sound insulation performance, mechanical properties and appearance changes (such as color change, surface cracking, etc.) of the samples were tested before and after aging.

[0069] 4. Environmental performance test: Detect the release of harmful substances (such as formaldehyde, benzene and other volatile organic compounds) in the sample in accordance with GB 18580-2017 standard.

[0070] (II) Analysis of test results

[0071] (1) Sound insulation performance

[0072] 1. Detailed data

[0073] 1. In the mid-to-low frequency band (100-1000Hz), the sound insulation of sample A is about 8dB higher than that of sample C at 100Hz, about 12dB higher at 500Hz, and about 15dB higher at 1000Hz; sample B is about 6dB higher than that of sample C at 100Hz, about 9dB higher at 500Hz, and about 12dB higher at 1000Hz.

[0074] 2. In the high frequency band (1000-5000Hz), sample A is about 5dB higher than sample C at 1000Hz, about 7dB higher at 2000Hz, and about 10dB higher at 5000Hz; sample B is about 4dB higher than sample C at 1000Hz, about 6dB higher at 2000Hz, and about 8dB higher at 5000Hz.

[0075] 3. The sound insulation of sample D in the entire test frequency range is significantly lower than that of the other three samples. The difference with samples A and B is more significant in the mid- and low-frequency bands. For example, at 500Hz, the sound insulation of sample D is about 15dB lower than that of sample A and about 10dB lower than that of sample B.

[0076] 2. Cause Analysis

[0077] 1. For sample A, the vinyl in the VMPA modifier forms a cross-linked structure with the solid waste plastic, which enhances the overall strength of the material, causing the sound waves to encounter a denser structure during propagation, resulting in increased energy loss. The methoxy and phenolic hydroxyl groups increase the flexibility and damping properties of the material. When sound waves cause the material to vibrate, these groups can convert sound energy into other forms of energy such as heat through their own deformation and intermolecular friction, thereby effectively improving the sound insulation effect. In addition, the hydrogen bonds formed by the phenolic hydroxyl groups and the hydroxyl groups on the surface of the inorganic fibers enhance the interfacial bonding force, reduce the reflection and transmission of sound waves at the interface between the solid waste plastic and the inorganic fibers, and further enhance the sound insulation performance.

[0078] 2. In sample B, the thioether bond of the BHMPTS modifier improves the processing performance of PVC, allowing it to form a more uniform structure during the molding process and reducing the impact of internal defects on the propagation of sound waves. The hydroxyl group improves the thermal stability of PVC, preventing defects such as pores caused by thermal degradation during processing and use, and ensuring the integrity of the material. The hydrogen bonds formed by the hydroxyl group and the surface active groups of the sound-absorbing filler enhance the dispersibility of the sound-absorbing filler in the matrix, so that the sound-absorbing filler can better play its sound-absorbing role. For example, the porous structure inside the expanded perlite powder and vermiculite powder can effectively absorb and scatter sound waves, thereby improving the sound insulation performance of the material.

[0079] (II) Mechanical properties

[0080] 1. Detailed data

[0081] 1. In terms of compressive strength, the average compressive strength of sample A is 12.5MPa, and the average compressive strength of sample D is 8MPa. Sample A is 56.25% higher than sample D. The average compressive strength of sample B is 10MPa, which is 25% higher than sample D.

[0082] 2. In terms of flexural strength, the average flexural strength of sample A is 17.5 MPa, and the average flexural strength of sample D is 10 MPa, which is 75% higher than that of sample D. The average flexural strength of sample B is 14 MPa, which is 40% higher than that of sample D.

[0083] 2. Cause Analysis

[0084] 1. In sample A, the cross-linked structure formed by the VMPA modifier significantly improves the strength and stability of the material, allowing the material to better resist deformation and damage when subjected to pressure and bending forces. The coupling agent improves the compatibility between the components, allowing the inorganic fibers to be evenly dispersed in the solid waste plastic matrix. The inorganic fibers can effectively bear external forces and play a reinforcing role, just like the steel bars in concrete, synergizing with the solid waste plastic matrix to improve the compressive and bending strength of the material.

[0085] 2. In sample B, the interaction between the sulfide bond and hydroxyl group in the BHMPTS modifier and the PVC molecular chain improves the overall performance of PVC and enhances its ability to resist external forces. The addition of stabilizers helps maintain the stability of the material during long-term stress and prevents the material from reducing its mechanical properties due to aging and other reasons. While improving the flexibility of the material, the plasticizer also helps to disperse external forces to a certain extent, allowing the material to deform better without breaking when subjected to pressure and bending, thereby improving the compressive and flexural strength.

[0086] (III) Weather resistance

[0087] 1. Detailed data

[0088] 1. After 1000-2000 hours of artificial weathering, the sound insulation performance retention rate of sample A is 85%-90% in the low and medium frequency bands and 80%-85% in the high frequency bands; the mechanical performance retention rate, compressive strength remains at 90%-95%, and bending strength remains at 85%-90%. In terms of appearance changes, there is only a slight lightening of color and no cracking on the surface.

[0089] 2. The sound insulation performance retention rate of sample B is 80%-85% in the low and medium frequency bands and 75% in the high frequency band

[0090] -80%; mechanical property retention rate, compressive strength maintained at 85%-90%, bending strength maintained at 80%-85%. There is a slight color change in appearance, and a small number of fine cracks on the surface.

[0091] 3. The sound insulation performance retention rate of sample C (rock wool board) is 70%-75% in the low and medium frequency bands and 65%-70% in the high frequency bands; the mechanical performance retention rate, compressive strength is maintained at 75%-80%, and bending strength is maintained at 70%-75%. The color is obviously darker in appearance, and there are more fine cracks on the surface.

[0092] 4. The sound insulation performance retention rate of sample D is 60%-65% in the low and medium frequency bands and 55% in the high frequency bands

[0093] -60%; mechanical property retention rate, compressive strength maintained at 65%-70%, bending strength maintained at 60%-65%. There are serious color changes in appearance, and there are many deeper cracks on the surface.

[0094] 2. Cause Analysis

[0095] 1. In sample A, the hot pressing treatment improves the density of the material and reduces the intrusion of media such as moisture and air, thereby reducing the performance degradation caused by environmental factors. The silicone water repellent coating on the surface effectively blocks the erosion of moisture, ultraviolet rays, etc. and protects the internal structure of the material. The stable structure formed by the good interaction between the VMPA modifier and each component also helps to maintain the performance of the material during the aging process.

[0096] 2. In sample B, the polar groups introduced by plasma surface treatment and the fire retardant coating applied have improved the weather resistance of the material to a certain extent. The polar groups enhance the hydrophilicity of the surface, making it difficult for water to accumulate on the surface of the material in a humid environment, reducing the performance degradation caused by water erosion. The fire retardant coating not only improves the fire resistance, but also protects the surface of the material to a certain extent, slowing down the damage to the material by ultraviolet rays, temperature changes, etc. The stabilizing effect of the BHMPTS modifier on PVC and its good combination with other components are also conducive to maintaining the performance of the material.

[0097] (IV) Environmental performance

[0098] 1. Detailed data

[0099] 1. The formaldehyde emission of sample A and sample B is less than 0.05mg / m 3 Benzene release is less than 0.02 mg / m 3 , in line with the requirements of GB 18580-2017 for E1 grade panels (formaldehyde emission ≤ 0.124 mg / m 3 Benzene release ≤ 0.05 mg / m 3 ).

[0100] 2. The formaldehyde emission of sample D is 0.1 mg / m 3 , benzene release is 0.03mg / m 3 , exceeding the standard limit of E1 grade panels, and after being placed for a long time, the release of formaldehyde and benzene tends to increase slowly.

[0101] 2. Cause Analysis

[0102] 1. During the preparation of samples A and B, on the one hand, the solid waste plastics themselves had less residual harmful substances after treatment, and on the other hand, the modifiers and additives used were all environmentally friendly materials, and the chemical reactions between the components during the processing were relatively sufficient, forming stable chemical bonds and reducing the release of harmful substances. For example, during the synthesis of VMPA modifiers and BHMPTS modifiers, the residual unreacted raw materials and by-products were reduced through reasonable reaction conditions and post-processing steps.

[0103] 2. Sample D has not been effectively modified, so the residual harmful substances in the solid waste plastic are difficult to be effectively controlled. During use, it may be due to environmental factors over time.

[0104] (such as temperature and humidity changes) cause harmful substances to be gradually released.

[0105] In summary, the sound insulation exterior wall materials prepared by the two new solutions show obvious advantages in sound insulation performance, mechanical properties, weather resistance and environmental protection performance. Compared with traditional materials and unmodified solid waste plastics, they have better comprehensive performance and have broad application prospects.

Claims

1. A method for preparing sound insulation material using solid waste plastics, characterized in that: The following steps are involved: S1 collects various types of solid waste plastics, including polyethylene (PE), polypropylene (PP), polystyrene (PS) and other waste plastics, classifies and screens them, crushes them into small particles with a particle size of 2-5mm, and prepares inorganic fibers, flame retardants and coupling agents; S2 synthesizes 4-vinyl-2-methoxyphenol acrylate (VMPA) modifier, mixes it with solid waste plastic particles at a mass ratio of 1:15-1:8, and simultaneously adds a coupling agent at a mass ratio of 1:10-1:5 to the modifier, and stirs at a high speed to evenly disperse the modifier; S3: adding the solid waste plastic particles treated with the modifier, the inorganic fiber and the flame retardant into a twin-screw extruder for melt blending, extruding and forming into a plate with a thickness of 1-3 cm and cooling and shaping; S4 performs hot pressing treatment on the cooled and shaped plate, the hot pressing temperature is 150-180°C, the pressure is 10-20MPa, the hot pressing time is 10-20 minutes, and then a silicone waterproofing agent coating is sprayed on the surface.

2. The method according to claim 1, characterized in that The synthesis method of the VMPA modifier comprises: S1 adds 4-hydroxy-3-methoxybenzaldehyde, hydroxyethyl acrylate, p-toluenesulfonic acid and toluene into a reaction kettle, heats to 80-100°C and reacts for 4-6 hours, and obtains the intermediate product 4-(2-hydroxyethyl)-2-methoxyphenol acrylate (HEMPA) after treatment; S2 reacts HEMPA, triethylamine, hydroquinone and acryloyl chloride, and obtains pure VMPA after treatment.

3. The method according to claim 1, characterized in that The inorganic fiber is glass fiber or rock wool fiber, the flame retardant is aluminum hydroxide or zinc borate, and the coupling agent is silane coupling agent KH-550 or titanate coupling agent NDZ-201.

4. A method for preparing sound insulation material using solid waste plastics, characterized in that: The following steps are involved: S1 collects polyvinyl chloride (PVC) solid waste plastics, crushes, cleans, dries, and prepares plasticizers, stabilizers, and sound-absorbing fillers; S2 prepares a bis(4-hydroxy-3-methylphenyl)sulfide (BHMPTS) modifier, mixes it with PVC solid waste particles at a mass ratio of 1:12-1:6, and simultaneously adds a plasticizer at a mass ratio of 2:1-3:1 to the modifier and a stabilizer at a mass ratio of 1:5-1:3 to the modifier, and kneads the components to make them uniformly dispersed; S3 adds the mixed material and the sound-absorbing filler into an open mixer for mixing, and then presses and forms the material into a sound-insulating exterior wall material plate through a flat vulcanizing machine; S4 performs plasma surface treatment on the formed plates and then applies intumescent fire retardant coating.

5. The method according to claim 4, characterized in that The preparation method of the BHMPTS modifier comprises: S1, under nitrogen protection, reacts 4-methylphenol, carbon disulfide and sodium hydroxide, and obtains the intermediate product bis(4-hydroxy-3-methylphenyl) disulfide (BHMPDS) by acidification, filtration and washing; S2: BHMPDS is reacted in a hydrogen atmosphere using a Raney nickel catalyst to obtain pure BHMPTS.

6. The method according to claim 4, characterized in that The plasticizer is dioctyl phthalate (DOP), the stabilizer is calcium stearate, and the sound-absorbing filler is expanded pearlite powder or vermiculite powder.

7. A sound insulation exterior wall material prepared by the method according to any one of claims 1 to 3, characterized in that: The VMPA modifier in the material forms a cross-linked structure with solid waste plastics through vinyl, the methoxy group and phenolic hydroxyl group improve the flexibility and damping performance of the material, the phenolic hydroxyl group enhances the interfacial bonding force with inorganic fibers, and the coupling agent improves the compatibility of each component.

8. A sound insulation exterior wall material prepared by the method according to any one of claims 4 to 6, characterized in that: The sulfide bond of the BHMPTS modifier in the material improves the processing performance of PVC, the hydroxyl group improves the thermal stability of PVC and enhances the bonding force with the sound-absorbing filler, the plasticizer improves flexibility, and the stabilizer improves long-term stability.

Citation Information

Patent Citations

  • Low cost and high efficient soundproof material and manufacturing method thereof

    CN103897262A

  • High-temperature-resistant and high-humidity-resistant environment-friendly sound insulation material and preparation method thereof

    CN113912972A

  • Composite soundproofing material

    WO2017079857A1

  • Flame-retardant and smoke-suppressing soft polyvinyl chloride composite material having good mechanical performance and preparation method therefor

    WO2020233028A1